Prevalence of oral cancer, oral potentially malignant disorders and other oral mucosal lesions in Cambodia. Issue 1 (2nd January 2018) - Chher, Tepirou; Hak, Sithan; Kallarakkal, Thomas George; Durward, Callum; Ramanathan, Anand; Ghani, Wan Maria Nabillah; Razak, Ishak Abdul; Harun, Masitah Hayati; Ashar, Nor Atika Md; Rajandram, Rama Krsna; Prak, Pisethraingsey; Hussaini, Haizal Mohd; et al.
ABSTRACT: Objectives: To obtain data on the prevalence of oral mucosal lesions (OMLs) among Cambodians, and to assess the relationship between known risk habits of oral diseases with prevalence of oral potentially malignant disorders (OPMDs). Design: This was a population-based, cross-sectional study whereby subjects were adults aged 18 years old and above. A workshop on the identification of OML was held to train and calibrate dental officers prior to data collection in the field. Sociodemographic and risk habits data were collected via face-to-face interview, whilst presence of OML and clinical details of lesions such as type and site were collected following clinical oral examination by the examiners. Data analysis was carried out using the Statistical Package for Social Science (SPSS) version 12.0. The association between risk habits and risk of OPMD was explored using logistic regression analysis. Results: A total of 1634 subjects were recruited. Prevalence of OML for this population was 54.1%. Linea alba was the most common lesion seen (28.7%). This study showed an overall OPMD prevalence of 5.6%. The most common type of OPMD was leukoplakia (64.8%), followed by lichen planus (30.8%). Subjects who only smoked were found to have an increased risk for OPMD of almost four-fold (RR 3.74, 95%CI 1.89–7.41). The highest risk was found for betel quid chewers, where the increased risk observed was more than six times (RR 6.75, 95%CI 3.32–13.72). Alcohol consumption on its own did not seem to confer an increased risk for OPMD, however when practiced concurrently with smoking, a significant risk of more than five times was noted (RR 5.69 95%CI 3.14–10.29). Conclusion: The prevalence of OML was 54.1%, with linea alba being the most commonly occurring lesion. Smoking, alcohol consumption and betel quid chewing were found to be associated with the prevalence of OPMD, which was 5.6%.